Hypopharyngeal schwannoma: A case report of a rare entity - Zhumabayeva, Aigerim; Hutinec, Zdenka; Bilic, Mario (ENT Updates, 2020)
We report the case of a 55-year old Caucasian female who presented with dysphagia after being operated for a brain glioblastoma. Fiberoptic endoscopy and magnetic resonance imaging showed a submucosal tumefaction of the posterior hypopharyngeal wall. Direct laryngoscopy and biopsy did not reveal a definitive diagnosis. The lesion was completely removed using a transoral C02 laser, and histopathological examination of the lesion showed a diagnosis of hypopharyngeal schwannoma. The patient recovered uneventfully and has remained clinically and radiologically disease-free for 6 months. Surgical excision and S100 protein immunohistochemistry remain the gold standards for treatment and diagnosis of hypopharyngeal schwannomas.